El entrenamiento multilateral es la base de habilidades tempranas transferibles y sin riesgo en niños (2019)
This study provides an overview of the practice of early sport sampling or multilateral training and the potential benefits associated with it. The main objective of this review is to investigate the literature on the effect of multi-training in the development of bio-motor skills and the mechanisms to influence the reduction of psychic, physical and social risks associated with early sports specialization. A systematic review of articles related to diversification and early sports specialization were carried out. 67 articles were identified through the search in the databases Sportdiscus and Google Scholar; It was carried out between the months of September 2017 and August 2018. For the selection of articles, the relevance and usefulness of the topic and the credibility or experience of the authors in the field were considered. The results of the review highlight the importance of multilateral training as a basis for early transferable skills and how early specialization presents multiple risks and is not a guarantee to reach elite in sport.